Hardplastic inclusion in elastic medium - Tsvelodub, Igor' Yurievich (Computational Continuum Mechanics, 2008)
The plane problems of determination of the stress-strain state of an isotropic elastic domain with a hardplastic inclusion are considered. It is shown that the stress field and the plastic zone are defined in a unique fashion. As an example, we consider a plane with an elliptic inclusion whose stress-strain state is uniform.